THE RELATIONSHIP OF FAMILY LIFE EDUCATION AND CHILDREN’S LEARNING ACHIEVEMENT - Sudiapermana, Elih; Muslikhah, Muslikhah; Rokhman, Nur (JESS (Journal of Educational Social Studies), 2020)
Family is the primary social institution, the first place where the process of education and learning for children occurs. Studies with various social and cultural backgrounds show that family factors have a significant contribution to children's learning achievement in school and their social-personal development. Sociologically, family has dimensions of structure and process. The research focuses on family process factors that significantly influence children's learning achievement in school. The study was involving 121 families who have 5th-grade elementary school children from two selected elementary schools to represent the characteristics of urban and suburban families. The data analysis was performed by Pearson Product moment correlation analysis. The results showed that the process factors which consist of intimacy in family life, the ability to adapt families to changes and aspirations of parents in children's education, are factors that significantly correlated with children's learning achievement in school.